(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
In the present research, an approach to the act of conversing in the academic environment is made in order to strengthen the communicative competencies of first semester students of the Faculty of Human Sciences and Fine Arts of the University of Quindío. It is pertinent to clarify that these are transversal competencies, that is, their development is necessary in all areas of knowledge. This work was carried out in four phases: in the first phase, a diagnosis was made, in which some deficiencies and strengths were evidenced with respect to argumentation and comprehension; in the second phase, strategies were designed for the development of the competencies; in the third phase, the intervention proposal was implemented. Finally, the evaluation was carried out, which was positive and the students were able to strengthen their competencies, interpreting, conversing and interacting in a critical manner.